The heart of flesh: Nietzsche on affects and the interpretation of the body - Fowles, C (Johns Hopkins University Press, 2020)
Nietzsche's philosophical psychology draws on a rich and extensive terminology. Integral to this terminology is the concept of an "affect." Although less widely discussed than the drives/instincts, affects are arguably every bit as important to Nietzsche's mature writings. Little attention, however, has been paid to the question of what Nietzsche thought affects were, such that they could do the considerable explanatory work he required of them. In this paper, I argue that by focusing on his reflections on both the psycho-physiological states to which we apply affect-words, and the sub-personal processes putatively involved in such episodes, we can draw out Nietzsche's understanding of affect. The picture that emerges comprises a form of somatic account, paired with an interpretive account of the mechanisms that subsume affective states under folk-psychological concepts and categories. Such a view, I hope to demonstrate, underpins some of Nietzsche's most prominent psychological claims.